Analyzing Hotel Customer Satisfaction Using Review Dataset: Insights and Implications for Service Improvement - Singgalen, Yerik Afrianto (Journal of Business and Economics Research (JBE), 2024)
This research investigates customer satisfaction at Meruorah Komodo Labuan Bajo through a comprehensive analysis of review data extracted from the Agoda platform. By examining 1,340 reviews, including 527 verified accounts, the study identifies key factors influencing guest experiences, such as service quality, room features, and location. The methodology comprised four stages: hotel selection, data scraping, data processing, and data interpretation. Findings indicate that premium room types, such as “The Signature Sea View Room,” consistently receive high satisfaction ratings, with 414 mentions (2.99%), highlighting the value placed on scenic views and superior amenities. Seasonal fluctuations and guest origins also impact satisfaction, with Indonesian guests strongly preferring familiarity, while international travelers prioritize diverse amenities. The data shows that 37 out of 203 accounts were domestic, while 17 were from the United States and Australia combined. The study reveals that 89% of domestic guests reported satisfaction, compared to varied expectations among international visitors. These insights suggest that tailored service strategies and enhancements in service consistency can further improve overall guest satisfaction. The research underscores the necessity of aligning service offerings with guest expectations to maintain a competitive edge in the dynamic hospitality industry.